2021
DOI: 10.1051/e3sconf/202127403003
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic transport in small livestock farms

Abstract: The article highlights the advantages and benefits of pipeline transport of liquid feed mixtures on small pig farms, the device and the principle of operation and technical characteristics of the improved rotor pump developed by the authors of the article. Methods of experimental research to determine the concentration of feed mixtures, the influence of the shape of the separator on the performance characteristics, the required power and the flow of an improved pump are presented. The results of the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This leads to an increase in pressure losses in the pipeline and to a decrease in the flow and speed of feed mixtures in the pipeline. In addition, the increase in losses is caused by friction between the liquid phase and solid particles of feed, as well as friction of solid particles of feed against the walls of the pipeline [7].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to an increase in pressure losses in the pipeline and to a decrease in the flow and speed of feed mixtures in the pipeline. In addition, the increase in losses is caused by friction between the liquid phase and solid particles of feed, as well as friction of solid particles of feed against the walls of the pipeline [7].…”
Section: Resultsmentioning
confidence: 99%
“…In works [5], it was shown that solar cells provide the specified energy when the ambient temperature is equal to 20 0 C, and when the solar cells are heated to 40-45 ℃, its capacity decreases by 15÷17%.…”
Section: Methodsmentioning
confidence: 99%
“…According to many scientists, this catastrophe could happen long before the crisis due to the lack of any fossil resources. All scientific progress is not capable of preventing ecological destruction, because artificial systems cannot replace the natural biological component of the environment and, therefore, cannot regulate the processes occurring in the biosphere [1,2,3].…”
Section: Introductionmentioning
confidence: 99%